1999
DOI: 10.1046/j.1365-2591.1999.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Canal configuration of the mesiobuccal root of the maxillary first molar of a Japanese sub‐population

Abstract: The proportion of cases with two canals in the mesiobuccal root of maxillary first molars from Japanese patients was high and similar to that described from studies of other ethnic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 11 publications
(10 reference statements)
7
91
1
13
Order By: Relevance
“…These reports depended on classic destructive examinations and were intended primarily for morphological classification. Weine et al 22) conducted observations based on new clinical criteria added to his own classification of root canals into 4 types 23) . The authors conducted pulp chamber opening and defined main root canal ramifications as root canals into which files could be inserted until they were seen at the root apex.…”
Section: Discussionmentioning
confidence: 99%
“…These reports depended on classic destructive examinations and were intended primarily for morphological classification. Weine et al 22) conducted observations based on new clinical criteria added to his own classification of root canals into 4 types 23) . The authors conducted pulp chamber opening and defined main root canal ramifications as root canals into which files could be inserted until they were seen at the root apex.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide bucco lingual dimensions of mesiobuccal roots, multiple canals are more common in these roots as compared to the distobuccal and palatal roots (Ahmad & Al-Jadaa, 2014). When treating maxillary first molars, a major cause of endodontic failure is the inability to properly locate, debride, or obturate the additional canals in the mesiobuccal root (Weine et al, 1999). Cleghorn et al (2006) reviewed the studies on the morphology of maxillary first molars and showed that 57 % of mesibuccal roots had 2 or more root canals.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent elements contribute to the variation found in root canal system of maxillary first molar, namely ethnic background, age, gender of the population studied, design, and methods of the study. 15,16 Variations in the root canal anatomy concerning distobuccal, distopalatal, and palatal roots are very infrequent (< 1%); nonetheless, their existence should be thoroughly scrutinized. 6 Recent advances in diagnostic technology have led to a paradigm shift, and therefore, CBCT is of paramount importance in dental imaging.…”
Section: Discussionmentioning
confidence: 99%